2016
DOI: 10.1002/ece3.1981
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and connectivity of morphological types of the broadcast‐spawning coral Galaxea fascicularis in the Nansei Islands, Japan

Abstract: Population connectivity resulting from larval dispersal is essential for the maintenance or recovery of populations in marine ecosystems, including coral reefs. Studies of species diversity and genetic connectivity within species are essential for the conservation of corals and coral reef ecosystems. We analyzed mitochondrial DNA sequence types and microsatellite genotypes of the broadcast‐spawning coral, Galaxea fascicularis, from four regions in the subtropical Nansei Islands in the northwestern Pacific Ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 63 publications
(144 reference statements)
2
12
1
Order By: Relevance
“…S10 ). The result presented here confirmed that the 12 corals used in the experiment were from the same lineage and were 100% identical to the sequences of mt-L1 type of Galaxea at GenBank (accession number: LC155810 and AB109376) 8 10 .…”
Section: Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…S10 ). The result presented here confirmed that the 12 corals used in the experiment were from the same lineage and were 100% identical to the sequences of mt-L1 type of Galaxea at GenBank (accession number: LC155810 and AB109376) 8 10 .…”
Section: Methodssupporting
confidence: 79%
“…Because of genetic differentiation 8 , their morphological characteristics are correlated with the length of the noncoding region between the mitochondrial genes cytb and nad2 9 . A more recent study reported several cryptic types found in G. fascicularis based on genetic information from microsatellite loci 8 10 . G. fascicularis shows intraspecific genetic diversity and connectivity and appears to have the potential for the recovery of populations after disturbance 8 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When different genotypes were determined to belong to the same MLL, the most common genotype was assigned 38 . However, if the most common genotype could not be determined ( e.g ., if two genotypes occurred in equal numbers), the genotype was set to zero 39 . We also calculated P SEX to estimate the possibility of coincidence of multilocus genotypes by sexual reproduction, using GenClone ver.…”
Section: Methodsmentioning
confidence: 99%
“…Galaxea fascicularis is a suitable model system to investigate Symbiodiniaceae metacommunity ecology, since it is a widely distributed generalist species acquiring symbionts from the settlement location (Baird et al 2009) and occurs at various depths on the reef. There are several genetic lineages within this species with little morphological differentiation (Nakajima et al 2016). Associations with Cladocopium ITS2 types C1, C1b, C2r, C21, C21a, C27, C3, C3d, C3u, C40, and C161, and Durusdinium types D1, D2, and D17 have been reported (GeoSymbio: Franklin et al 2012, Zhou et al 2012, indicating a rather flexible relationship potentially varying according to exogenous characteristics.…”
Section: Introductionmentioning
confidence: 93%